Synthesis of Coated Urea and Study of its Impact on Growth and Yield of Maize - . Lalchhuanawmi; M. R. Backiyavathy; Sharmila Rahale (Research Highlights in Agricultural Sciences Vol. 6, 2022)
In this study, three distinct types of urea fertilizer coatings with ethyl cellulose and starch-super absorbent polymer were synthesized and their release pattern as well as their effectiveness in field condition was also closely studied. A column experiment was set up to study the release pattern of the coated urea. Only 40% (64.2 mg N kg-1 soil) of the nitrogen was released by the double-coated urea (EC+SAP) in the first 24 hours, which exhibited the highest slow-release pattern. In a field experiment conducted in Vaiyampalayam, Coimbatore, India, Urea coated with EC + starch-SAP (100% RDF) has the highest dry matter production, followed by Urea coated with EC + starch-SAP (75% RDF) with values of 9519 and 9116 kg ha-1, respectively.